ANALISIS KINERJA MANAJEMEN USAHA EKONOMI KELURAHAN SIMPAN PINJAM (UEK-SP) MENGGUNAKAN PENDEKATAN Risk-Based Management Rating (Studi Kasus UEK-SP Bersama Sejahtera Pekanbaru) - Nando, Alfri; Muwardi, Didi; ', Rosnita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Economic Business Village Savings and Loans (UED-SP) is a rural institution in the field of finance to support productive economic activities of the village. The purpose of this study was to analyze the Performance Management Using Risk-Based Management Approach Rating And Quality Service In-SP UEK Tangkerang Tengah Prosperity Village Middle District of Marpoyan Damai Pekanbaru. This study uses primary data and secondary data was conducted using survie. Data were collected from questionnaires and 30 management members UEK-SP using purposive sampling. Data analysis includes General Manajenem (strategy / objectives, structure, systems and leadership), Risk Management (liquidity risk, credit risk, operational risk, legal risk and risk committee) as well as aspects of quality of service (tangible, reliability, responsiveness, assurance / certainty and concern). The results show that the performance management Shared Prosperity UEK-SP using a calculation predicate HEALTHY reward system with a credit score of 86, while the service quality of management UEK-SP Shared Prosperity predicate VERY GOOD with a score of 2576.   Key Words  :UEK-SP, Risk-Based Management Rating, managemant performance , service qulity